PKCε controls the traffic of β1 integrins in motile cells - Ivaska, Johanna (Oxford University Press, 2002)
Protein kinase C (PKC) has been implicated in β1 integrin-mediated cell migration. Expression of the novel PKC isoform, PKCε, in PKCε(–/–) cells is shown here to stimulate directional migration of cells towards β1 integrin substrates in a manner dependent on PKC catalytic activity. On PKC inhibition, integrin β1 and PKCε become reversibly trapped in a tetraspanin (CD81)-positive intracellular compartment, correlating with reduced haptotaxis. Immunofluorescence and pulse labelling studies indicate that this is a previously uncharacterized recycling compartment trapped by inhibition of PKC. Electron microscopy demonstrated the co-localization of PKCε and integrin β1 on the vesicular membranes. Finally, using a reconstituted in vitro system, the dissociation of PKCε from these vesicles is shown to be dependent on both the presence of cytosolic components and energy, and on PKC catalytic activity. The evidence presented indicates that PKCε controls an internal traffic step that under uninhibited conditions permits the recycling of β1 integrin, contributing to cell motility.